Cancer nanotheranostics - Gopinath, P.; Uday Kumar, S.; Matai, Ishita; Bhushan, Bharat; Malwal, Deepika; Sachdev, Abhay; Dubey, Poornima; SpringerLink (Online service). (Singapore Springer Singapore, 2015)
This Brief provides a clear insight of the recent advances in the field of cancer theranostics with special emphasis upon nano scale carrier molecules (polymeric, protein and lipid based) and imaging agents (organic and inorganic).
Electronic reproduction.
Keywords: Cancer -- Treatment; Electronic books